Digitalisasi Daya Tarik Wisata Alam Melalui Video Promosi Virtual Tour Di Desa Duda Timur Karangasem Bali - Ida Bagus Nyoman Krisna Prawira Yuda; I Nengah Subadra; Novandra Lucky Prabawa; Ni Kadek Noni Purnama Dewi; Dewi Siti Anjani (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
The development of natural tourism also has great prospects in the future. This is supported by the social media trend that is currently developing among young people. The rapid trend of social media today means that the flow of information is also moving very quickly. One of the areas that is still rarely visited even though it is an interesting tourist attraction on the island of Bali is Duda Timur Village, which is located in Karangasem Regency. Some of the natural attractions that Duda Timur village has are, Jagasatru waterfall, Brahma statue, Putung hill, Beji Dedari and take a sip. The aim of this activity is to introduce the tourist attractions of the village to tourists. The tourism village digitalization program through making promotional videos in the form of a 360 virtual tour was carried out by taking pictures and videos at Jagasatru and Beji Dedari Waterfalls, then students and KKNT accompanying lecturers implemented it on social media such as YouTube, TikTok, Instagram and websites.